The contribution of livestock business and utilization of biogas on the income of farmer's family in Boyolali Regency - Sutrisno Hadi Purnomo; Ayu Intan Sari; Endang Tri Rahayu; Shanti Emawati (Livestock and Animal Research, 2022)
Objective: Farm businesses not only produce output in the form of meat, eggs, and milk, but also produce livestock manure, which can be used as biogas to achieve business efficiency and optimization. This study aims to determine the contribution of cattle farming by utilizing livestock manure into biogas on the income of the farmer's family.Methods: The research was conducted in Boyolali Regency, namely in Musuk, Ampel, Cepogo, and Sambi Districts. Respondents of this study were dairy and beef cattle breeders who had processed livestock manure into biogas with a total of 60 respondents. The data analysis method used is descriptive quantitative analysis, income analysis, and business contribution analysis.Results: The results of the study indicate that the income of beef cattle farming with an average maintenance scale of 3 animals is 458,083 IDR/month, while the value of dairy farming business income with a scale of 2 animals is 749,083 IDR /month. Beef cattle farmer family income 5.497.000 IDR/month and 8.989.000 IDR/month for the family income of dairy farmers. The contribution of beef cattle business to family income is 29.93%, and 36.88% is for dairy cattle.Conclusions: The conclusion is the contribution of beef cattle farming by using livestock manure into biogas is still low, which is below 30%, categorized as a small business. Livestock business income is not only influenced by the sale of cows and milk, but also from the utilization of waste into biogas (7.1-8.0%).